Answer: see below
Explanation:
The standard form of an exponential equation is: y = a(b)ˣ where
- a is the initial value
- b is the rate
Growth:
Exponential growth is where the final value (y) is greater than the initial value (a).
An example would be the spreading of a rumor:
You tell 1 person (a = 1) who then tells 2 people each minute (b = 2). How many people will they have spread the rumor to after 5 minutes (x = 5)?
y = 1(2)⁵
= 32
Decay:
Exponential decay is where the final value (y) is less than the initial value (a).
An example would be the decrease of bacteria in a person:
A person has 100 bacteria (a = 1) who takes a pill that is supposed to cut in half the number of bacteria each hour (b = 1/2). How many bacteria will the person have after 2 hours (x = 2)?
![y=100\bigg((1)/(2)\bigg)^2\\\\\\.\quad =100\bigg((1)/(4)\bigg)\\\\\\.\quad = 25](https://img.qammunity.org/2021/formulas/mathematics/college/nq3buzni5porkmu0rghajnl9yd2mhztw56.png)